Exploring mechanisms and origins of reduced dispersal in island Komodo dragons. Issue 1891 (21st November 2018) - Jessop, Tim S.; Ariefiandy, Achmad; Purwandana, Deni; Ciofi, Claudio; Imansyah, Jeri; Benu, Yunias Jackson; Fordham, Damien A.; Forsyth, David M.; Mulder, Raoul A.; Phillips, Benjamin L.
Abstract : Loss of dispersal typifies island biotas, but the selective processes driving this phenomenon remain contentious. This is because selection via, both indirect (e.g. relaxed selection or island syndromes) and direct (e.g. natural selection or spatial sorting) processes may be involved, and no study has yet convincingly distinguished between these alternatives. Here, we combined observational and experimental analyses of an island lizard, the Komodo dragon ( Varanus komodoensis, the world's largest lizard), to provide evidence for the actions of multiple processes that could contribute to island dispersal loss. In the Komodo dragon, concordant results from telemetry, simulations, experimental translocations, mark-recapture, and gene flow studies indicated that despite impressive physical and sensory capabilities for long-distance movement, Komodo dragons exhibited near complete dispersal restriction: individuals rarely moved beyond the valleys they were born/captured in. Importantly, lizard site-fidelity was insensitive to common agents of dispersal evolution (i.e. indices of risk for inbreeding, kin and intraspecific competition, and low habitat quality) that consequently reduced survival of resident individuals. We suggest that direct selection restricts movement capacity (e.g. via benefits of spatial philopatry and increased costs of dispersal) alongside use of dispersal-compensating traits (e.g. intraspecific niche partitioning) to constrain dispersal in island species.